Preparation and Characterization of Magnetite Nanoparticle using Green Synthesis - Lahure Pranita; Jain Preeti (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
The studies show the synthesis of nanomagnetite, in lab by biological method as it does not involve any harmful chemicals and are easily available in the market. In the present work, magnetite (Fe3O4) nanoparticles were synthesized by using green biosynthetic method. The band- gap of the Fe3O4-NPs was investigated by UV-Vis Absorption & FTIR Spectroscopy are in range of 2.17-3.40 eV. The average particle diameter & its grain size are determined by the Effective Mass Approximation Formula and XRD technique, which came to be 1-2 nm and grain size 4-14.3nm respectively. . Also conductivity of prepared samples was calculated using the TDS Conductivity Meter, the results shows that the prepared nanoparticle are conductive in nature. The nanoparticles synthesized by this biosynthesis method can potentially useful in various applications.